A novel approach on cooperation and coordination building within a multi-agent system for complex diagnostics - Timalsina, Arun K. (Nepalese Journal of Engineering, 2005)
Any diagnostic problem solving requires expert knowledge of that subject. As the degree of complexity of the problem rises, knowledge growth should be in both ways extensive and intensive, which is not possible to achieve with a single knowledge source. The software agent being an entity designed to cooperate with others, the expert knowledge can be viewed as a collection of agents. The intensive knowledge can be achieved through the depth of the knowledge in a single agent where as the extensive knowledge can be achieved through the number of agents. The price for this extensive knowledgeable multi agents' configuration is conflict resolution and cooperation building. In this paper, concise insight model to deal with cooperation and coordination within a Multi Agent System (MAS) has been analyzed. A complex case of cystic fibrosis has been presented to show that how this whole system is applied in medical diagnostics. Keywords: agent, cooperative problem solving, diagnostics, evidence function, notion of diagnosis. Nepalese Journal of Engineering Vol.1(1) 2005 pp.10-17